Resposta:
A alternativa correta é c).
Explicação passo-a-passo:
[tex] {( \sqrt{2} )}^{x + 1} = 4 \times \sqrt{2} \\ \\ = > x + 1 = log_{ \sqrt{2} }(4 \times \sqrt{2} ) \\ \\ = > x + 1 = log_{ \sqrt{2} }(4) + log_{ \sqrt{2} }( \sqrt{2} ) \\ \\ = > x + 1 = \frac{ log_{2}(4) }{ log_{2}( \sqrt{2} ) } + 1 \\ \\ = > x + 1 = \frac{ log_{2}( {2}^{2} ) }{ log_{2}( {2}^{ \frac{1}{2} } ) } + 1 \\ \\ = > x + 1 = \frac{2 \times log_{2}(2) }{ \frac{1}{2} \times log_{2}(2) } + 1 \\ \\ = > x + 1 - 1= \frac{2}{ \frac{1}{2} } \\ \\ = > x = 4[/tex]
Copyright © 2025 ELIBRARY.TIPS - All rights reserved.
Lista de comentários
Resposta:
A alternativa correta é c).
Explicação passo-a-passo:
[tex] {( \sqrt{2} )}^{x + 1} = 4 \times \sqrt{2} \\ \\ = > x + 1 = log_{ \sqrt{2} }(4 \times \sqrt{2} ) \\ \\ = > x + 1 = log_{ \sqrt{2} }(4) + log_{ \sqrt{2} }( \sqrt{2} ) \\ \\ = > x + 1 = \frac{ log_{2}(4) }{ log_{2}( \sqrt{2} ) } + 1 \\ \\ = > x + 1 = \frac{ log_{2}( {2}^{2} ) }{ log_{2}( {2}^{ \frac{1}{2} } ) } + 1 \\ \\ = > x + 1 = \frac{2 \times log_{2}(2) }{ \frac{1}{2} \times log_{2}(2) } + 1 \\ \\ = > x + 1 - 1= \frac{2}{ \frac{1}{2} } \\ \\ = > x = 4[/tex]